Effect of Introduction of Exogenous Strain Acidithiobacillus thiooxidans A01 on Structure and Function of Adsorbed and Planktonic Microbial Consortia During Bioleaching of Low-Grade Copper Sulfide - Liu, Yi; Wang, Junjun; Hou, Haijun; Chen, Gang; Liu, Hongwei; Liu, Xueduan; Shen, Li (Frontiers in Microbiology, 2020)
The introduction of Acidithiobacillus thiooxidans A01 strengthens the positive interactions between physiologically distinct microorganisms and enhances the bioleaching ability of the consortium. However, the effect of introducing an exogenous strain, A. thiooxidans A01 on the structure and function of the adsorbed and planktonic microbial consortia during bioleaching of low-grade copper sulfide remains unclear. In this study, A. thiooxidans A01 was introduced into an indigenous leaching microbial community on the 0th (group B), 24th (group C), and 36th day (group D). Results revealed that the copper leaching efficiency was highest in group D, in which the Cu2+ concentration in the solution reached 251.5 mg/L on day 48, which was 18.5% higher than that of the control (group A, no addition of A. thiooxidans A01). Restriction fragment length polymorphism (RFLP) analysis of the microbial community in group D revealed the presence of Leptospirillum ferriphilum, Acidithiobacillus ferrooxidans, Acidithiobacillus caldus, Sulfobacillus sp., Acidiphilium spp., and Acidithiobacillus albertensis before introduction of A. thiooxidans A01 on the 36th or 48th day; however, A. albertensis was absent on day 48 in group A. Further, the proportion of dominant A. caldus, L. ferriphilum, and A. ferrooxidans became altered. The results of real-time PCR in group D showed that A. thiooxidans A01 was primarily adsorbed on the surface of the ore, with the adsorption reaching the maxima on day 42; while the free A. thiooxidans A01 in solution grew slowly, reaching its maximum concentration on day 45. Compared with that in the control group, the abundance of both free and attached A. caldus and Sulfobacillus sp. decreased following the introduction of A. thiooxidans A01, while that of L ferriphilum, A. ferrooxidans, and Acidiphilium sp. increased. Functional gene arrays data indicated that the abundance of genes involved in sulfide and iron oxidation in L. ferriphilum and A. ferrooxidans, as well as that of the metal (loid) resistance genes of A. ferrooxidans, L. ferriphilum, and Acidiphilium sp. increased, while the abundance of genes involved in sulfur metabolism in A. caldus and Sulfolobus spp. decreased. Taken together, these results provide useful information for application of bioleaching of copper sulfide in industry.